2010
DOI: 10.1590/s0103-84782010005000052
|View full text |Cite
|
Sign up to set email alerts
|

Comparação dos testes de virusneutralização contra os genótipos 1 e 2 do vírus da diarreia viral bovina (BVDV-1 e BVDV-2) em bovinos de rebanhos naturalmente infectados

Abstract: Comparação dos testes de virusneutralização contra os genótipos 1 e 2 do vírus da diarreia viral bovina (BVDV-1 e BVDV-2) em bovinos de rebanhos naturalmente infectadosComparison of virusneutralization tests against genotypes 1 and 2 of the bovine viral diarrhoea virus (BVDV-1 and BVDV-2) in cattle of naturally infected herds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Furthermore , Table 3 also shows that, in most of the properties, the iELISA identified the prevalence of anti-BVDV Ab better than VN, which suggests that the iELISA was able to identify the genotype BVDV-2 since only the NADL strain (BVDV type 1 genotype) was identified using the VN test. Dias et al (2010) investigated the prevalence of anti-BVDV-1 Ab and anti-BVDV-2 Ab in 1,925 serum samples obtained from herds from different regions of the São Paulo state that were naturally infected and unvaccinated against BVDV. In different production systems, previous studies detected a larger prevalence of seropositive animals (62.8% of animals reactive to the two genotypes, 2.65% reacted only against BVDV-1, and 3.5% only to BVDV-2) than that reported in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore , Table 3 also shows that, in most of the properties, the iELISA identified the prevalence of anti-BVDV Ab better than VN, which suggests that the iELISA was able to identify the genotype BVDV-2 since only the NADL strain (BVDV type 1 genotype) was identified using the VN test. Dias et al (2010) investigated the prevalence of anti-BVDV-1 Ab and anti-BVDV-2 Ab in 1,925 serum samples obtained from herds from different regions of the São Paulo state that were naturally infected and unvaccinated against BVDV. In different production systems, previous studies detected a larger prevalence of seropositive animals (62.8% of animals reactive to the two genotypes, 2.65% reacted only against BVDV-1, and 3.5% only to BVDV-2) than that reported in this study.…”
Section: Resultsmentioning
confidence: 99%
“…These results proved the dissemination of the two genotypes in the herds of the state of São Paulo and showed that it is of fundamental importance to include both genotypes in the VN tests performed by Brazilian laboratories. As well as the use of Brazilian isolates strains, since there is huge antigenic variability in relation to North American and European BVDV strains (DIAS et al, 2010;DUBOVI, 2013). It is worth noting that most of the Brazilian laboratories that perform the VN test for BVDV use only BVDV-1 strains of North American origin (Singer and NADL) (OIE, 2015).…”
Section: Resultsmentioning
confidence: 99%